A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade and a preparation method thereof
By using a composite water-based polyurethane emulsion on the leading edge of the wind power blade, the problem of traditional films being easily worn and have limited corrosion resistance in extreme environments is solved, and higher wear and corrosion resistance is achieved, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411794188.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional membranes are prone to wear and have limited corrosion resistance in extreme environments of the leading edge of wind power blades, making it difficult to meet the needs of long-term use.
A composite aqueous polyurethane emulsion was used to prepare an wear-resistant and corrosion-resistant film. The graphite phase carbon nitride was modified by peeling the ultrasonic auxiliary solvent, and carboxymethyl chitosan and fillers composed of carbon nanotubes and silica were added to enhance the dispersion and binding force of the film, and enhance the wear and corrosion resistance.
It significantly improves the wear resistance and corrosion resistance of the film, extends the service life of the leading edge film of the wind power blade, reduces maintenance costs, and gives the film a certain self-cleaning ability and photoaging resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of films and relates to a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade and a preparation method thereof. Background Art
[0002] As a key component of the wind power generation system, wind turbine blades are exposed to complex and changeable natural environments for a long time. The leading edge of the wind turbine blades is subject to erosion by wind, rain, ultraviolet rays and other factors. The membrane used must have excellent wear and corrosion resistance to ensure the long-term operation and power generation efficiency of the blades. Traditional membranes often have problems such as easy wear and limited corrosion resistance when dealing with the extreme environment of the leading edge of wind turbine blades, making it difficult to meet the needs of long-term use. Therefore, it is very necessary to explore a new type of high-efficiency wear-resistant and corrosion-resistant membrane for the leading edge of wind turbine blades. Summary of the invention
[0003] The object of the present invention is to provide a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade and a preparation method thereof, which has the characteristics of good wear resistance and corrosion resistance.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the wear-resistant and corrosion-resistant film is obtained by curing, granulating, blowing and film-forming a composite water-based polyurethane emulsion, and cooling and shaping.
[0006] The formula of the composite waterborne polyurethane emulsion is as follows: in parts by weight, 70-80 parts of waterborne polyurethane emulsion, 5-10 parts of modified graphite phase carbon nitride, 6-8 parts of waterborne polyurethane curing agent, 3-5 parts of composite filler, 0.8-1 part of leveling agent, 0.3-0.5 part of defoaming agent, and 0.3-0.5 part of wetting dispersant.
[0007] Wherein, the preparation method of the modified graphite phase carbon nitride is as follows:
[0008] S1-1: 20-30 parts by weight of melamine were placed in a muffle furnace for calcination at a temperature of 550 °C and a heating rate of 5 °C / min, and then placed in a ball mill for 1.5 h at a ball mill speed of 300-400 r / min, and then washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder A;
[0009] S1-2: Powder A was added to a 40-50% by mass isopropanol solution, subjected to ultrasonic treatment for 4 h, washed with deionized water, and dried in a vacuum oven at 60 °C for 12 h to obtain powder B.
[0010] S1-3: Powder B is added to deionized water so that the solid-liquid mass ratio is 1:(8-10), 5 wt% carboxymethyl chitosan solution is added dropwise, and the mixture is stirred at 45-55 °C for 6 h. The mixture is washed with deionized water and centrifuged at a centrifugal speed of 5000 r / min for 10 min. The mixture is placed in a vacuum drying oven at 60 °C and dried for 12 h to obtain the modified graphite phase carbon nitride.
[0011] The preparation method of the composite filler is as follows:
[0012] In parts by weight, 2 to 3 parts of carbon nanotubes are added to 80 to 90 parts of an ethanol solution with a mass fraction of 80%, ultrasonicated for 20 to 30 minutes, 5 to 7 parts of ammonia water are added, stirred at a speed of 500 to 600 r / min for 30 minutes, 1.5 to 2.5 parts of tetraethyl orthosilicate are added, stirred at 50°C for 4 hours, then 0.1 to 0.3 parts of a silane coupling agent KH550 are added, stirred at 50°C for 30 minutes, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the composite filler.
[0013] Furthermore, the calcination time in S1-1 is 4 h.
[0014] Furthermore, the frequency of the ultrasound in S1-2 is 6 to 8 kHz.
[0015] Furthermore, the concentration of the carboxymethyl chitosan solution in S1-3 is 2 M.
[0016] Furthermore, the defoaming agent is one of BYK022, BYK024 and BYK028.
[0017] Furthermore, the leveling agent is one of Tego410 and Tego450.
[0018] Furthermore, the wetting and dispersing agent is one of Tego250, BYK348, and BYK349.
[0019] Furthermore, the concentration of the ammonia water is 6 M.
[0020] A method for preparing a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the specific steps of the preparation method are as follows:
[0021] S10-1: Modified graphite phase carbon nitride and composite filler were mixed according to the formula, and ball milled in a ball mill for 1 h at a ball milling speed of 200-300 r / min. The milled powder was added to the aqueous polyurethane emulsion, and stirred at a speed of 800-900 r / min for 30 min to obtain dispersion C;
[0022] S10-2: Add the leveling agent, defoaming agent, wetting dispersant and waterborne polyurethane curing agent to the dispersion C, increase the speed to 1000-1100 r / min, and homogenize for 30 min to obtain a composite waterborne polyurethane emulsion;
[0023] S10-3: The composite waterborne polyurethane emulsion is injected into the mold and coated to determine the thickness, dried at 120-130 °C for 4-5 h, extruded into granules through a twin-screw extruder at a speed of 130 r / min and a temperature of 170-180 °C, and then blown into a film and cooled to shape, so as to prepare the wear-resistant and corrosion-resistant film.
[0024] Graphite carbon nitride is a material with high hardness and good wear resistance, which can significantly improve the mechanical properties of waterborne polyurethane film. In addition, as a photocatalytic material, graphite carbon nitride can generate photogenerated electron-hole pairs with redox ability under visible light irradiation. Adding it to polyurethane can significantly improve the film's resistance to light aging and give the film a certain self-cleaning ability. However, the graphite carbon nitride prepared by the traditional calcination method has some defects due to the close stacking of the layers, such as poor dispersibility, small specific surface area and low visible light utilization. Therefore, the dispersibility of graphite carbon nitride in the film and the binding force with polyurethane are improved by gentle and convenient ultrasonic-assisted solvent exfoliation modification, thereby enhancing the wear resistance of the film. The introduction of carboxymethyl chitosan, with its advantages of biodegradability, biocompatibility, antibacterial and economical, is not only used as a material for the anti-corrosion barrier layer of active metals, but its rich oxygen-containing functional groups can also effectively break the van der Waals force between graphite carbon nitride sheets, further reduce the agglomeration of graphite carbon nitride in polyurethane, promote the uniform dispersion of graphite carbon nitride and optimize the interfacial compatibility. In addition, carboxymethyl chitosan also has good film-forming properties. By forming a uniform and complete composite film on the surface of the substrate, it effectively shields the migration process of corrosive ions, prevents direct contact between the corrosive medium and the substrate, and significantly improves the corrosion resistance of the polyurethane film. Not only does it significantly improve the corrosion resistance of the film, it also extends the service life of the leading edge film of the wind turbine blade and reduces maintenance costs.
[0025] The composite filler is composed of carbon nanotubes and silicon dioxide. In an ammonia environment, ethyl orthosilicate is in situ hydrolyzed on the surface of carbon nanotubes to generate silicon dioxide, which significantly enhances the interaction between carbon nanotubes and silicon dioxide and improves the overall performance of the composite filler. The introduction of silane coupling agent as a bridge between the composite filler and polyurethane greatly enhances the compatibility between the two, effectively improves the uniformity and stability of the film, and ensures that the composite filler can give full play to its performance advantages. The composite filler combines the good impact resistance of carbon nanotubes with the hardness and wear resistance of silicon dioxide, so that the membrane can show higher strength and durability when it is subjected to the complex stresses of the leading edge of the wind turbine blade. In addition, the addition of the composite filler also effectively fills the tiny pores that may be generated in the membrane, further improving the corrosion resistance of the membrane.
[0026] Beneficial effects of the present invention:
[0027] (1) The dispersibility of graphite carbon nitride in waterborne polyurethane film and its binding force with polyurethane were improved by a gentle and convenient ultrasonic-assisted solvent exfoliation modification technology. The introduction of carboxymethyl chitosan further reduced the agglomeration of graphite carbon nitride in polyurethane, promoted its uniform dispersion and optimized the interfacial compatibility; at the same time, carboxymethyl chitosan formed a uniform and complete composite film on the surface of the substrate, effectively shielding the migration process of corrosive ions and significantly improving the corrosion resistance of the polyurethane film. In addition, the photocatalytic property of graphite carbon nitride generates photogenerated electron-hole pairs under visible light irradiation, giving the film a certain self-cleaning ability and significantly improving the film's resistance to light aging.
[0028] (2) The composite filler is made of carbon nanotubes and silica through in-situ hydrolysis, which significantly enhances the interaction between carbon nanotubes and silica and improves the overall performance of the composite filler. The introduction of silane coupling agent as a bridge between the composite filler and polyurethane greatly enhances the compatibility between the two, effectively improves the uniformity and stability of the film, and ensures that the composite filler can fully exert its performance advantages. The composite filler combines the good impact resistance of carbon nanotubes with the hardness and wear resistance of silica, so that the film can exhibit higher strength and durability when subjected to the complex stresses of the leading edge of the wind turbine blade. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] In the embodiments of the present invention and the comparative examples:
[0031] Melamine: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 108-78-1;
[0032] Isopropyl alcohol: purchased from Ningbo Huatuo Chemical Co., Ltd., CAS No. 67-63-0;
[0033] Carboxymethyl chitosan: purchased from Shanghai PUCO Biotechnology Co., Ltd., CAS No. 83512-85-0;
[0034] Waterborne polyurethane emulsion: purchased from Dongguan Xuhua New Material Technology Co., Ltd., brand name XH-PU229;
[0035] Carbon nanotubes: purchased from Shanghai Liantian Materials Technology Co., Ltd., CAS number 308068-56-6;
[0036] Ethanol: purchased from Changshu Hongsheng Fine Chemical Co., Ltd., CAS No. 64-17-5;
[0037] Ethyl orthosilicate: purchased from Zhangjiagang Longtai Chemical Co., Ltd., CAS No. 78-10-4;
[0038] Ammonia: purchased from Zhuzhou Dayuan Industrial Co., Ltd., CAS No. 1336-21-6;
[0039] Silane coupling agent KH550: purchased from Nanjing Quanxi New Materials Co., Ltd., CAS No. 919-30-2;
[0040] BYK022, BYK024, BYK028, BYK348, BYK349: purchased from Guangzhou Ligou New Materials Co., Ltd.;
[0041] Tego410, Tego450, Tego250: purchased from Shanghai Buding Chemical Co., Ltd.
[0042] Waterborne polyurethane curing agent: purchased from Hefei Hengtian New Material Technology Co., Ltd.
[0043] Example 1
[0044] A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the wear-resistant and corrosion-resistant film is obtained by curing, granulating, blowing and film-forming a composite water-based polyurethane emulsion, and cooling and shaping.
[0045] The formula 1 of the composite waterborne polyurethane emulsion is as follows: in parts by weight, 75 parts of waterborne polyurethane emulsion, 7 parts of modified graphite phase carbon nitride, 7 parts of waterborne polyurethane curing agent, 4 parts of composite filler, 0.9 parts of Tego410, 0.4 parts of BYK022, 0.4 parts of Tego250,
[0046] Wherein, the preparation method of the modified graphite phase carbon nitride is as follows:
[0047] S1-1: 25 parts by weight of melamine were placed in a muffle furnace for calcination at a temperature of 550 °C, a heating rate of 5 °C / min, and a calcination time of 4 h, and then placed in a ball mill for 1.5 h at a ball mill speed of 350 r / min, and then washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder A;
[0048] S1-2: Powder A was added to a 45% by mass isopropanol solution, subjected to ultrasonic treatment for 4 h at a frequency of 7 kHz, washed with deionized water, and dried in a vacuum oven at 60 °C for 12 h to obtain powder B.
[0049] S1-3: Powder B is added to deionized water so that the solid-liquid mass ratio is 1:9, and 5 wt% carboxymethyl chitosan solution is added dropwise, wherein the concentration of the carboxymethyl chitosan solution is 2 M. The mixture is stirred at 50°C for 6 h, washed with deionized water and centrifuged at a centrifugal speed of 5000 r / min for 10 min. The mixture is placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the modified graphite phase carbon nitride.
[0050] The preparation method of the composite filler is as follows:
[0051] In parts by weight, 2.5 parts of carbon nanotubes are added to 85 parts of ethanol solution with a mass fraction of 80%, ultrasonicated for 25 minutes, 6 parts of 6 M ammonia water are added, stirred at a speed of 550 r / min for 30 minutes, 2 parts of tetraethyl orthosilicate are added, stirred at 50°C for 4 hours, then 0.2 parts of silane coupling agent KH550 are added, stirred at 50°C for 30 minutes, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the composite filler.
[0052] A method for preparing a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the specific steps of the preparation method are as follows:
[0053] S10-1: Modified graphite phase carbon nitride and composite filler were mixed according to formula 1, and ball milled in a ball mill for 1 h at a ball milling speed of 250 r / min. The ball milled powder was added to the aqueous polyurethane emulsion, and stirred at a speed of 850 r / min for 30 min to obtain dispersion C;
[0054] S10-2: Add Tego410, BYK022, Tego250 and waterborne polyurethane curing agent to dispersion C, increase the speed to 1050 r / min, and homogenize for 30 min to obtain a composite waterborne polyurethane emulsion;
[0055] S10-3: The composite waterborne polyurethane emulsion is injected into the mold and coated to determine the thickness, dried at 125°C for 4.5 hours, extruded into granules through a twin-screw extruder at a speed of 130 r / min and a temperature of 175°C, and then blown into a film and cooled to shape, thereby preparing the wear-resistant and corrosion-resistant film.
[0056] Example 2
[0057] A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the wear-resistant and corrosion-resistant film is obtained by curing, granulating, blowing and film-forming a composite water-based polyurethane emulsion, and cooling and shaping.
[0058] The formula 2 of the composite water-based polyurethane emulsion is as follows: in parts by weight, 70 parts of water-based polyurethane emulsion, 5 parts of modified graphite phase carbon nitride, 6 parts of water-based polyurethane curing agent, 3 parts of composite filler, 0.8 parts of Tego450, 0.3 parts of BYK024, 0.3 parts of BYK348,
[0059] Wherein, the preparation method of the modified graphite phase carbon nitride is as follows:
[0060] S1-1: 20 parts by weight of melamine were placed in a muffle furnace for calcination at a temperature of 550 °C, a heating rate of 5 °C / min, and a calcination time of 4 h, and then placed in a ball mill for 1.5 h at a ball mill speed of 300 r / min, and then washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder A;
[0061] S1-2: Powder A was added to a 40% by mass isopropanol solution, subjected to ultrasonic treatment for 4 h at a frequency of 6 kHz, washed with deionized water, and dried in a vacuum oven at 60 °C for 12 h to obtain powder B;
[0062] S1-3: Powder B is added to deionized water so that the solid-liquid mass ratio is 1:8, and 5 wt% carboxymethyl chitosan solution is added dropwise, wherein the concentration of the carboxymethyl chitosan solution is 2 M. The mixture is stirred at 45°C for 6 h, washed with deionized water and centrifuged at a centrifugal speed of 5000 r / min for 10 min. The mixture is placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the modified graphite phase carbon nitride.
[0063] The preparation method of the composite filler is as follows:
[0064] In parts by weight, 2 parts of carbon nanotubes are added to 80 parts of ethanol solution with a mass fraction of 80%, ultrasonicated for 20 minutes, 5 parts of 6 M ammonia water are added, stirred at a speed of 500 r / min for 30 minutes, 1.5 parts of tetraethyl orthosilicate are added, stirred at 50°C for 4 hours, then 0.1 parts of silane coupling agent KH550 are added, stirred at 50°C for 30 minutes, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the composite filler.
[0065] A method for preparing a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the specific steps of the preparation method are as follows:
[0066] S10-1: Modified graphite phase carbon nitride and composite filler were mixed according to formula 2, and ball milled in a ball mill for 1 h at a ball milling speed of 200 r / min. The ball milled powder was added to the aqueous polyurethane emulsion and stirred at a speed of 800 r / min for 30 min to obtain dispersion C;
[0067] S10-2: Add Tego450, BYK024, BYK348 and waterborne polyurethane curing agent to dispersion C, increase the speed to 1000 r / min, and homogenize for 30 min to obtain a composite waterborne polyurethane emulsion;
[0068] S10-3: The composite waterborne polyurethane emulsion is injected into the mold and coated to determine the thickness, dried at 120°C for 4 h, extruded into granules through a twin-screw extruder at a speed of 130 r / min and a temperature of 170°C, and then blown into a film and cooled to shape, thereby preparing the wear-resistant and corrosion-resistant film.
[0069] Example 3
[0070] A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the wear-resistant and corrosion-resistant film is obtained by curing, granulating, blowing and film-forming a composite water-based polyurethane emulsion, and cooling and shaping.
[0071] The formula 3 of the composite water-based polyurethane emulsion is as follows: in parts by weight, 80 parts of water-based polyurethane emulsion, 10 parts of modified graphite phase carbon nitride, 8 parts of water-based polyurethane curing agent, 5 parts of composite filler, 1 part of Tego410, 0.5 parts of BYK028, 0.5 parts of BYK349,
[0072] Wherein, the preparation method of the modified graphite phase carbon nitride is as follows:
[0073] S1-1: 30 parts by weight of melamine were placed in a muffle furnace for calcination at a temperature of 550 °C, a heating rate of 5 °C / min, and a calcination time of 4 h, and then placed in a ball mill for 1.5 h at a ball mill speed of 400 r / min, and then washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder A;
[0074] S1-2: Powder A was added to a 50% by mass isopropanol solution, subjected to ultrasonic treatment for 4 h at a frequency of 8 kHz, washed with deionized water, and dried in a vacuum oven at 60 °C for 12 h to obtain powder B.
[0075] S1-3: Powder B is added to deionized water so that the solid-liquid mass ratio is 1:10, and 5 wt% carboxymethyl chitosan solution is added dropwise, wherein the concentration of the carboxymethyl chitosan solution is 2 M. The mixture is stirred at 55°C for 6 h, washed with deionized water and centrifuged at a centrifugal speed of 5000 r / min for 10 min. The mixture is placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the modified graphite phase carbon nitride.
[0076] The preparation method of the composite filler is as follows:
[0077] In parts by weight, 3 parts of carbon nanotubes were added to 90 parts of ethanol solution with a mass fraction of 80%, ultrasonicated for 30 minutes, 7 parts of 6 M ammonia water were added, stirred at a speed of 600 r / min for 30 minutes, 2.5 parts of tetraethyl orthosilicate were added, stirred at 50°C for 4 hours, and then 0.3 parts of silane coupling agent KH550 were added, stirred at 50°C for 30 minutes, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the composite filler.
[0078] A method for preparing a polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, wherein the specific steps of the preparation method are as follows:
[0079] S10-1: Modified graphite phase carbon nitride and composite filler were mixed according to formula 3, and ball milled in a ball mill for 1 h at a ball milling speed of 300 r / min. The ball milled powder was added to the aqueous polyurethane emulsion and stirred at a speed of 900 r / min for 30 min to obtain dispersion C;
[0080] S10-2: Add Tego410, BYK028, BYK349 and aqueous polyurethane emulsion to dispersion C, increase the speed to 1100 r / min, and homogenize for 30 min to obtain a composite aqueous polyurethane emulsion;
[0081] S10-3: The composite waterborne polyurethane emulsion is injected into the mold and coated to a certain thickness, dried at 130°C for 5 h, extruded into granules through a twin-screw extruder at a speed of 130 r / min and a temperature of 180°C, and then blown into a film, cooled and shaped to prepare the wear-resistant and corrosion-resistant film.
[0082] Comparative Example 1
[0083] The preparation process of modified graphite phase carbon nitride does not go through step S1-2, and the remaining steps are consistent with Example 1.
[0084] Comparative Example 2
[0085] The preparation process of modified graphite phase carbon nitride does not go through step S1-3, and the remaining steps are consistent with Example 1.
[0086] Comparative Example 3
[0087] No composite filler was added, and the remaining steps were the same as those in Example 1.
[0088] Performance Test:
[0089] The wear resistance of the films prepared in the examples and comparative examples was measured according to GB / T 1768-2006; the corrosion resistance of the films was measured according to GB / T 1771-2007.
[0090] The experimental data are recorded in the following table:
[0091]
[0092] It can be seen from the data of the examples and comparative examples that the wear resistance and corrosion resistance of the membrane can be significantly improved by using ultrasonic assisted solvent stripping and modifying the graphite phase carbon nitride with carboxymethyl chitosan, and adding a filler composed of carbon nanotubes and silicon dioxide.
[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade, characterized in that: The wear-resistant and corrosion-resistant film is obtained by curing, granulating, blowing and film-forming the composite waterborne polyurethane emulsion, and cooling and shaping. The formula of the composite waterborne polyurethane emulsion is as follows: in parts by weight, 70-80 parts of waterborne polyurethane emulsion, 5-10 parts of modified graphite phase carbon nitride, 6-8 parts of waterborne polyurethane curing agent, 3-5 parts of composite filler, 0.8-1 part of leveling agent, 0.3-0.5 part of defoaming agent, and 0.3-0.5 part of wetting dispersant. Wherein, the preparation method of the modified graphite phase carbon nitride is as follows: S1-1: 20-30 parts by weight of melamine were placed in a muffle furnace for calcination at a temperature of 550°C and a heating rate of 5°C / min, and then placed in a ball mill for 1.5 h at a ball mill speed of 300-400 r / min, and then washed with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain powder A; S1-2: Powder A was added to a 40-50% by mass isopropanol solution, subjected to ultrasonic treatment for 4 h, washed with deionized water, and dried in a vacuum oven at 60 °C for 12 h to obtain powder B. S1-3: Powder B is added to deionized water so that the solid-liquid mass ratio is 1:(8-10), 5 wt% carboxymethyl chitosan solution is added dropwise, and the mixture is stirred at 45-55 °C for 6 h. The mixture is washed with deionized water and centrifuged at a centrifugal speed of 5000 r / min for 10 min. The mixture is placed in a vacuum drying oven at 60 °C and dried for 12 h to obtain the modified graphite phase carbon nitride. The preparation method of the composite filler is as follows: In parts by weight, 2 to 3 parts of carbon nanotubes are added to 80 to 90 parts of an ethanol solution with a mass fraction of 80%, ultrasonicated for 20 to 30 minutes, 5 to 7 parts of ammonia water are added, stirred at a speed of 500 to 600 r / min for 30 minutes, 1.5 to 2.5 parts of tetraethyl orthosilicate are added, stirred at 50°C for 4 hours, then 0.1 to 0.3 parts of a silane coupling agent KH550 are added, stirred at 50°C for 30 minutes, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the composite filler.
2. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The calcination time in S1-1 is 4 h.
3. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The frequency of ultrasound in S1-2 is 6~8 kHz.
4. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The concentration of the carboxymethyl chitosan solution in S1-3 is 2 M.
5. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The defoamer is one of BYK022, BYK024 and BYK028.
6. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The leveling agent is one of Tego410 and Tego450.
7. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The wetting and dispersing agent is one of Tego250, BYK348 and BYK349.
8. The polyurethane wear-resistant and corrosion-resistant film for the leading edge of a wind turbine blade according to claim 1, characterized in that: The concentration of the ammonia water is 6 M.
9. A method for preparing a polyurethane wear-resistant and corrosion-resistant film for a leading edge of a wind turbine blade according to any one of claims 1 to 8, characterized in that: The specific steps of the preparation method are as follows: S10-1: Modified graphite phase carbon nitride and composite filler were mixed according to the formula, and ball milled in a ball mill for 1 h at a ball milling speed of 200-300 r / min. The milled powder was added to the aqueous polyurethane emulsion, and stirred at a speed of 800-900 r / min for 30 min to obtain dispersion C; S10-2: Add the leveling agent, defoaming agent, wetting dispersant and waterborne polyurethane curing agent to the dispersion C, increase the speed to 1000-1100 r / min, and homogenize for 30 min to obtain a composite waterborne polyurethane emulsion; S10-3: The composite waterborne polyurethane emulsion is injected into the mold and coated to determine the thickness, dried at 120-130 °C for 4-5 h, extruded into granules through a twin-screw extruder at a speed of 130 r / min and a temperature of 170-180 °C, and then blown into a film and cooled to shape, so as to prepare the wear-resistant and corrosion-resistant film.
Citation Information
Patent Citations
Wear-resistant and corrosion-resistant polyurethane film for front edge of wind power blade and preparation method thereof
CN118580674A
Waterborne polyurethane coating for laminated aluminum plate and preparation method of waterborne polyurethane coating
CN118703104A